Effect of Water Hyacinth Leaf Flour (Eichhornia crassipes) Fermented by Aspergillus niger on the Growth, Survival Rate and Blood Profile of Sangkuriang Catfish (Clarias gariepinus) - Febri Ariyanto; Rudy Agung Nugroho; Retno Aryani; Hetty Manurung; Rudianto Rudianto (Aceh Journal of Animal Science, 2023)
Catfish sangkuriang (Clarias gariepinus) is one of the aquaculture commodities with great potential to be developed in Indonesia to support the demand for feed. Efforts to reduce dependence on imported feed raw materials for fish feed is continued. Water hyacinth (Eichhornia crasspies) leaf which contains phytochemical compounds such as flavonoids, tannins, steroids and saponins is an alternatif raw material for fish pellet component. This study aimed to determine the addition of fermented water hyacinth leaf meal in fish feed on the growth, survival rate, and blood profile of sangkuriang catfish. In total 150 fish (Average initial weight 5.45 ± 0.02 g) were randomly divided into triplicates of five groups, containing 10 fishes per group. Group one is a control group, P1 (10% of non fermented water hyacinth leaf meal), while P2, P3 and P4  were treatment groups of fish fed with 10 , 15, and 20% fermented water hyacinth leaf meal by Aspergillus niger. At the end of the 42 days of treatment, growth, survival rate, and blood profile of all fish were determined. The results showed that the addition of 10% water hyacinth leaf meal fermented by Aspergillus niger had an effect on the growth of final weight, body weight gain and spesific growth rate (p 0.05) in comparison to all groups. However, the addition of any concentration of water hyacinth leaf meal did not affect on the feed conversion ratio and survival rate value. Further, the addition of water hyacinth leaf meal had a significant effect (p 0.05) on the erythrocytes, leukocytes and hemoglobin of fish, but did not show a significant effect on the values of hematocrit and platelets.